Alterations in innate immunity reactants and carbohydrate and lipid metabolism precede occurrence of metritis in transition dairy cows. (February 2016) - Dervishi, Elda; Zhang, Guanshi; Hailemariam, Dagnachew; Goldansaz, Seyed Ali; Deng, Qilan; Dunn, Suzanna M.; Ametaj, Burim N.
Abstract: The overall purpose of the present study was to search for early screening biomarkers of disease state. Therefore the objectives of this study were to evaluate metabolites related to carbohydrate metabolism, acute phase proteins, and proinflammatory cytokines in the blood of transition dairy cows starting at − 8 weeks before calving. Blood samples were collected from 100 multiparous Holstein dairy cows during − 8, − 4, disease diagnosis, + 4 and + 8 weeks relative to parturition. Six healthy cows and 6 cows that showed clinical signs of metritis were selected for serum analysis. Overall the results showed that cows with metritis had greater concentration of lactate, interleukin-6 (IL-6), tumor necrosis factor (TNF), and serum amyloid A (SAA) versus healthy cows throughout the experiment. The disease was associated with decrease in milk production and fat: protein ratio. Cows with metritis showed alteration in metabolites related to carbohydrate metabolism, acute phase proteins, and proinflammatory cytokines starting at − 8 weeks prior to parturition and appearance of clinical signs of the disease. This study suggests a possible use of cytokines as early markers of disease in dairy cows. Highlights: We screened biomarkers of disease in the blood of transition dairy cows. We examined the level of serum metabolites, cytokines, and acute phase proteins. Lactate, IL-6, TNF, SAA can be used as early indicators of inflammatory processes. Cytokines might be used as early markers of disease in dairy cows. Cows with metritis showed alteration in metabolites − 8 weeks before parturition.